Gambaran Kelainan Refraksi Mata Pada Anak Di SD N 3 Bantul - Muhammad Alfian Muzakki; Kuntadi Wahyu Widadi; Mia Ayu Nadia (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
There are parents disobey if their child has symptoms of myopia. If the eye examination is not conducted. This research aim to help parents identify the visual impairment disorders in children at SD N3 Bantul. The eye examination was carried out by using a subjective examination method. Based on the results, the data show 30 students in grades 5 A and B at SD N 03 Bantul have refractive errors. 6 students aged 11 years have myopia refractive error. 3 participants with a PD of 58mm were OD S -1.00 OS Plano with the dominant eye of the left eye. 5 participants with PD 58 showed an ODS of S-1.00. 5 participants including OD S-1.00 OS Plano. 5 participants namely ODS S -0.25 D PD 58. 3 participants namely OD S -0.50 OS Plano PD 58. 9 participants namely ODS S -0.50 D.